The Influence of Investment Decisions, Funding Decisions, Free Cash Flow, and Financial Sustainability on Shareholder Value in the Food and Beverage Sector Listed on the Indonesian Stock Exchange for the Period 2018-2022 - Cindy Rahmawati Putri Utami; Ratih Kusumawardhani; Risal Rinofah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to find out more clearly about the factors that influence investment decisions, funding decisions, free cash flow, and financial sustainability on shareholder value in the food and beverage sector listed on the Indonesia Stock Exchange for the period 2018-2022. The number of food and beverage sector companies listed on the IDX in 2018-2022 is 94, but only 45 companies match the predetermined criteria. The methods used in this research are descriptive statistics, classical assumption tests, multiple linear analysis, and hypothesis testing with data analysis using SPSS 25. This study uses the dependent variable shareholder value and the independent variables are investment decisions, funding decisions, free cash flow, and financial sustainability. The results of this study indicate that partial testing (T-test), investment decision variables, funding decision variables, free cash flow variables, and financial sustainability variables show negative results or have no significant effect on shareholder value.